2018
DOI: 10.1111/jphp.12902
|View full text |Cite
|
Sign up to set email alerts
|

Development of an enteric nanoparticle of marine sulfated polysaccharide propylene glycol alginate sodium sulfate for oral administration: formulation design, pharmacokinetics and efficacy

Abstract: The study showed that enteric-coated formulation of PSS had the intestinal-targeted absorption and improved pharmacodynamics, which indicated that enteric PSS-NP could be developed into a new formulation product in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Faced with this challenge, Li et al tested a new formulation of PSS in the form of enteric-coated nanoparticle (enteric PSS-NP) [107]. The study showed that the PSS nanoparticle had targeted intestinal absorption and improved pharmacodynamics.…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…Faced with this challenge, Li et al tested a new formulation of PSS in the form of enteric-coated nanoparticle (enteric PSS-NP) [107]. The study showed that the PSS nanoparticle had targeted intestinal absorption and improved pharmacodynamics.…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…More recent studies have sought a way to improve the bioavailability and efficacy of PSS in the body, since the absorption of this compound can sometimes be impaired because of its high MW. Faced with this challenge, Li et al tested a new formulation of PSS in the form of enteric-coated nanoparticle (enteric PSS-NP) [ 107 ]. The study showed that the PSS nanoparticle had targeted intestinal absorption and improved pharmacodynamics.…”
Section: Structure and Functionmentioning
confidence: 99%
“…When compared to the PSS solution, enteric PSS-NP had an improved effectiveness in controlling body weight. These data indicate that enteric PSS-NP could be promising in terms of product development in the future [ 107 ].…”
Section: Structure and Functionmentioning
confidence: 99%
“…Propylene glycol alginate sodium sulfate (PSS) is a marine sulfated polysaccharide derivative that is used to prevent and treat ischemic cardio-cerebrovascular diseases and hyperlipidemia in China for almost 30 years. [6][7][8] Several studies have reported that PSS can inhibit cancer cell metastasis in vitro through inhibition of angiogenesis and platelet activation. 6,9 Accumulating evidence suggests that PSS is an ideal carrier material for selective loading or efficient co-loading of small molecules and even nanoparticles due to its favorable physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Several studies have reported that PSS can inhibit cancer cell metastasis in vitro through inhibition of angiogenesis and platelet activation. 6,9 Accumulating evidence suggests that PSS is an ideal carrier material for selective loading or efficient co-loading of small molecules and even nanoparticles due to its favorable physical and chemical properties. 10 However, a critical obstacle of cancer treatment is the inefficient delivery of therapeutic agents due to the high spatiotemporally heterogeneous in the complicated and dense tumor stroma.…”
Section: Introductionmentioning
confidence: 99%